Pengaruh Jenis Bagian Daging Babi dan Penambahan Tepung Terigu Terhadap Sifat Fisikokimiawi Pork Nugget - Ina Maria Fransisca, Thomas Indarto Putut Suseno, Sutarjo Surjoseputro, (Jurnal Teknologi Pangan dan Gizi, 2007)
Parts of pork meat that can be made into pork nugget are shoulder, loin, and leg because each part has different physicochemical characteristics, e.g. colour, texture, and chemical composition. Filler is one of ingredients needed in making nuggets. Fillers that usually used are wheat flour, corn flour, and rice flour. This research’s objectives were to know the effects of different parts of pork meat and wheat flour’s concentration to physicochemical and sensory characteristics of pork nugget. Experimental design was Nested Randomized Design, which wheat flour’s concentration i.e. 10%, 15%, 20%, 25% was nested in different parts of pork meat i.e. shoulder, loin, and leg. All data has been analyzes with ANOVA and LSD test. Effectiveness test is used to get the best treatments. The research results showed that wheat flour’s concentration did not give a significant effect (p=0,05) on cohesiveness and Water Holding Capacity (WHC) but it gave a significant effect (p=0,05) on hardness, fat, protein, and water content. Best treatments were pork shoulder nugget using 15% wheat flour, pork loin nugget using 10% wheat flour, and pork leg nugget using 10% wheat flour.